2012
DOI: 10.1371/journal.pgen.1002998
|View full text |Cite
|
Sign up to set email alerts
|

Variants Affecting Exon Skipping Contribute to Complex Traits

Abstract: DNA variants that affect alternative splicing and the relative quantities of different gene transcripts have been shown to be risk alleles for some Mendelian diseases. However, for complex traits characterized by a low odds ratio for any single contributing variant, very few studies have investigated the contribution of splicing variants. The overarching goal of this study is to discover and characterize the role that variants affecting alternative splicing may play in the genetic etiology of complex traits, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
61
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 68 publications
3
61
0
Order By: Relevance
“…In the present study, we detected significant linkage between murine genetic variants and AS events for various genes, including Apobec3, Il3ra, Clec7a, and Apobec1, congruent with previous studies that demonstrated association between individual AS events and SNPs in the human genome (Cartegni et al 2002;Narla et al 2005;Lee et al 2012). AS can result in nonfunctional protein isoforms (Lango Allen et al 2010), which may alter cellular physiological states (David et al 2010;Gao and Cooper 2013).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the present study, we detected significant linkage between murine genetic variants and AS events for various genes, including Apobec3, Il3ra, Clec7a, and Apobec1, congruent with previous studies that demonstrated association between individual AS events and SNPs in the human genome (Cartegni et al 2002;Narla et al 2005;Lee et al 2012). AS can result in nonfunctional protein isoforms (Lango Allen et al 2010), which may alter cellular physiological states (David et al 2010;Gao and Cooper 2013).…”
Section: Discussionsupporting
confidence: 91%
“…AS can be due to variations at the splice site (cis) or to polymorphic or differentially expressed splice factors, enhancers, and repressors (trans) Lee et al 2012;Zaphiropoulos 2012). Therefore, based on the distance from the corresponding splice site, the sQTL can be categorized as cis or trans.…”
Section: Distinct Loci Modulate Isoform Usage In Murine Macrophagesmentioning
confidence: 99%
See 1 more Smart Citation
“…3B, Right). DNA sequence variation as causative in disease has also been implicated in other studies (27)(28)(29). In summary, the strengths of each approach (model mice with mixed genetic backgrounds and transcriptomics) are synergized, whereas their respective drawbacks are minimized.…”
Section: Discussionmentioning
confidence: 99%
“…However, posttranscriptional modifications, including alternative splicing, are important in creating a transcriptome with diverse biological functions (Matlin et al 2005). Mutations that lead to disruption of splicing play an important role in tissueand disease-specific pathways (López-Bigas et al 2005;Ward and Cooper 2010;Lee et al 2012;DeBoever et al 2015;Li et al 2016c).…”
mentioning
confidence: 99%